Morphometric analysis for gender determination using maxillary sinus on panoramic radiographs- a retrospective study - Dawrani , Palak; Handa , Hina; Shinde, Christopher Vinay; Sharma, . Shubha (Journal of Neonatal Surgery, 2025)
Human identification in forensic investigations relies on the assessment of biological parameters such as age, sex, and stature. When conventional identification methods are limited, forensic dentistry plays a crucial role. Sex determination is a primary step in skeletal identification, and craniofacial structures—particularly the maxillary sinus—exhibit marked sexual dimorphism. Panoramic radiography provides a practical and non-invasive method for evaluating these structures. To analyze the dimensions of right and left maxillary sinuses on panoramic radiographs of adult subjects and assess their usefulness in gender determination. A retrospective cross-sectional study conducted at the Department of Oral Medicine and Radiology, People’s Dental Academy, Bhopal, Madhya Pradesh, India. Digital panoramic radiographs of 800 individuals aged 20–60 years with complete permanent dentition were evaluated. Maxillary sinus height and width on both sides were measured using calibrated PLANMECA ROMEXIS 2.9.2.R software. Radiographs with sinus pathology, positioning errors, or history of maxillary surgery were excluded. Data analysis was performed using SPSS version 22. Mean and standard deviation were calculated, and comparisons between genders were made using the Independent Student’s t-test. A p value <0.05 was considered statistically significant. All maxillary sinus dimensions were significantly greater in males compared to females on both sides (p <0.001). Height and width measurements of the right and left maxillary sinuses demonstrated consistent sexual dimorphism. Maxillary sinus dimensions measured on panoramic radiographs show significant sexual dimorphism and can serve as a reliable adjunct in gender determination for forensic identification